2021
DOI: 10.1016/j.jtcme.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Mentha spicata L. essential oil, phytochemistry and its effectiveness in flatulence

Abstract: Flatulence as the continuous feeling of abdominal distension is equal to “Nafkh” in Iranian Traditional Medicine. Nafkh is believed to derive from the amount of stomach temperature, humidity of food or abnormal humidity in digestive tract and their interactions. Mentha spicata as cool and spicy plant with astringent and digestive property is recommended for treatment of flatulence. The information was extracted from accessible international databases, traditional books, electronic resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
3
25
0
5
Order By: Relevance
“…Mentha piperita is an aromatic herb with analgesic and tranquilizing effects. The analgesic effect of peppermint can be due to its main compounds like Carvone, Limonene, and Menthol 18,19. Menthol in peppermint affects Kappa Opioid receptors and soothe the pain in return.…”
Section: Introductionmentioning
confidence: 99%
“…Mentha piperita is an aromatic herb with analgesic and tranquilizing effects. The analgesic effect of peppermint can be due to its main compounds like Carvone, Limonene, and Menthol 18,19. Menthol in peppermint affects Kappa Opioid receptors and soothe the pain in return.…”
Section: Introductionmentioning
confidence: 99%
“…and its essential oils are popularly used in food, cosmetics, and pharmaceutical industries (20). Despite the different species of the plant, several studies have named carvone as its main active component (21). Mentha sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have suggested that the transient receptor potential cation channel subfamily M (melastatin) member 8 (TRPM8) and transient receptor potential cation channel, subfamily A, member 1 (TRPA1) are implicated in pain relief (analgesia) and sensation of cooling [ 73 , 75 ]. In Ayurvedic medicine, some Mentha species were used to mitigate skin problems and headaches [ 76 ]. In vitro studies showed that peppermint essential oil and menthol acted as smooth muscle relaxants via blocking Ca 2+ influx through L-type Ca 2+ channels [ 77 , 78 ].…”
Section: Properties Of the Mentha Genusmentioning
confidence: 99%